Study on Influences of Rear-Wheel Turn Angle to Performance of Four Wheel Steering (4WS) Vehicle - ALIF SYAHRIZAD BIN RAMLI, ALIF SYAHRIZAD (Universiti Teknologi PETRONAS, 2010)
The main objective of this project is to study on influences of rear-wheel turn angle to the performances of 4-wheel-steering (4WS) vehicle. As to determine either the evaluated performances of 4WS is either an advantage or disadvantage, thus, a datum is required. Therefore 2-wheel-steering (2WS) system is also included in the study since the 2WS system does not utilize the rear-wheel turn angle (zero rear-wheel turn angles). The core problem statement implies in this project is what are the advantages and disadvantages of 4WS vehicle; is the influences of rear-wheel turn angle to 4WS does affecting in good or bad way? Thus, the first scope done in this project is the configuration of the 4WS system shall be established to correlate how the rear-wheel shall turn accordingly with respect to the steering-wheel and the front-wheel turn angle. For this study, Honda’s 4WS system is used. K.N Spentzas and I. Alkhazali stated that to study 4WS vehicle, simplification shall be made and one of it is the used of two-degree-of-freedom bicycle model. This model is very useful for analyzing the kinematics of the vehicle (i.e. turning radius, vehicle side-slip). However, when it comes to dynamic parameters (i.e. wheels side-slip angle, lateral velocity, yaw velocity), three-degree-of-freedom is desired since certain elements is essential to get a qualified data. By referring to recent literatures made related to this project, the quality of the data, methodology and the procedures to produce them are also been checked beforehand to ensure that the project is done professionally. The study includes few critical parameters such as turning radius, yaw velocity, lateral velocity, and side-slip angles that are necessary to evaluate how the rear-wheel turn angle affects the vehicle’s performances by comparing those findings between 4WS and 2WS vehicles.